A slow lopsided bar in the interacting dwarf galaxy IC 3167. Issue 1 (9th July 2022) - Cuomo, V; Corsini, E M; Morelli, L; Aguerri, J A L; Lee, Y H; Coccato, L; Pizzella, A; Buttitta, C; Gasparri, D
ABSTRACT: We present surface photometry and stellar kinematics of IC 3167, a dwarf galaxy hosting a lopsided weak bar and infalling into the Virgo cluster. We measured the bar radius and strength from broad-band imaging and bar pattern speed by applying the Tremaine–Weinberg method to stellar-absorption integral-field spectroscopy. We derived the ratio of the corotation radius to bar radius (${\cal {R}}=1.7^{+0.5}_{-0.3}$ ) from stellar kinematics and bar pattern speed. The probability that the bar is rotating slowly is more than twice as likely as that the bar is fast. This allows us to infer that the formation of this bar was triggered by the ongoing interaction rather than the internal processes.